Quantum Tunnelling in Nanostructures: Mechanisms, Applications, and Experimental Observations (International Journal of Scientific Research in Science and Technology, 2025)
Quantum tunneling, a fundamental phenomenon in quantum mechanics, enables particles to traverse potential barriers that would be classically insurmountable. In the realm of nanostructures, where dimensions approach the de Broglie wavelength of electrons, tunneling effects become significantly pronounced and technologically exploitable. This paper explores the principles of quantum tunneling in nanostructures such as quantum dots, nanowires, and tunnel junctions. We review key literature, experimental methodologies, and recent advancements in the measurement and control of tunneling processes. The study highlights the implications of tunneling for modern electronics, quantum computing, and energy devices. Experimental and computational findings confirm the critical role of barrier width, material properties, and coherence in determining tunneling efficiency. Our discussion suggests future research directions in optimizing tunneling-based devices for enhanced performance and energy efficiency of quantum dots tunning.